Economic and technical optimization by the implementation of precast slabs applied on Sente building - Saavedra Salinas, Lizbeth Bretania (2023)
The present research sets out the economic and technical evaluation of two construction systems used in the actual industry, and includes the comparison of cost, time lapse of the slabs construction and the level of construction solid waste. The analyzed systems were: i) Precast beams and ii) Precast slabs, evaluated in Sente Building. In addition, the criteria of technological level is presented which support the reduction in execution time achieved by the precast slabs system in comparison with the precast beam system. As a part of the economic evaluation, the costs associated with every constructive procedure and execution period were estimated. The results showed that, in comparison with precast beams system, the precast slabs system achieved a reduction of the cost building cost in 3.45%, a reduction in time execution of 10% accumulated in both building towers, and ultimately, the precast slab system reduces the quantity of solid waste of construction as requires 18.5% minus of in-situ concrete.